2018
DOI: 10.1080/15226514.2017.1365344
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution and chemical forms of cadmium in Morus alba L.

Abstract: Morus alba L. (mulberry) is a perennial woody tree and a species with great potential for Cd phyremediation owing to its large biomass and extensive root system. The mechanisms involved in Cd detoxification were investigated by analyzing the subcellular distribution and chemical forms of Cd in mulberry in the present study. These results indicated that 53.27-70.17% of Cd mulberry accumulated was stored in the root and only about 10% were in the leaves. Lots of the Cd was located in the cell wall of the mulberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 29 publications
2
9
0
2
Order By: Relevance
“…This proves that the compartmentalisation of soluble fractions is an important mechanism for Eucalyptus to accumulate and tolerate Cd [ 141 , 142 ]. Tian et al showed that the main Cd enrichment sites in Sedum alfredii were the cortex and mesophyll tissue, and most of them were located in the vacuole [ 143 ], which is consistent with the findings of Huang et al [ 117 ] and Zhang et al [ 11 ].…”
Section: The Mechanisms Of Plant Enrichment Of CDsupporting
confidence: 82%
See 1 more Smart Citation
“…This proves that the compartmentalisation of soluble fractions is an important mechanism for Eucalyptus to accumulate and tolerate Cd [ 141 , 142 ]. Tian et al showed that the main Cd enrichment sites in Sedum alfredii were the cortex and mesophyll tissue, and most of them were located in the vacuole [ 143 ], which is consistent with the findings of Huang et al [ 117 ] and Zhang et al [ 11 ].…”
Section: The Mechanisms Of Plant Enrichment Of CDsupporting
confidence: 82%
“…The root cell wall is mainly composed of cellulose, hemicellulose, and pectin, which are rich in hydroxyl, thiol, and carboxyl functional groups. These functional groups can bind to Cd 2+ so that Cd can be retained in the root cell wall [ 117 , 120 ]. Cd in roots mainly accumulates in the cortical tissues of root tips and root hairs.…”
Section: The Mechanisms Of Plant Enrichment Of CDmentioning
confidence: 99%
“…In poplar, willow and Morus alba L., Cd sequestrations into cell walls, vacuoles and golgi apparatus have been found to facilitate Cd detoxification (Vollenweider et al, 2006;He et al, 2013;Huang et al, 2018;Bi et al, 2020). It has been reported that Cd could be chelated by S-containing compounds, such as glutathione (GSH) and phytochelatin, and then transported into vacuoles (He et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Para o NF, verificou-se redução de forma linear, com decréscimo de 25,5% na maior dose (9 mg kg -1 ) em relação ao controle (Figura 1c). O decréscimo do número de folhas, de forma global, ocasiona a redução da área foliar, portanto, reduz a taxa fotossintética, consequentemente ocorrerá uma menor produção e translocação de fotoassimilados para as diferentes partes da planta (raiz, caule, folha e fruto), fato este que altera seu crescimento (TAIZ & ZEIGER, 2017;SU et al, 2017;HUANG et al, 2018).…”
Section: Resultsunclassified